2016
DOI: 10.4166/kjg.2016.68.2.70
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Management of Poor Bowel Preparation: A Survey Study

Abstract: Background/Aims: There are no established guidelines for bowel preparation formulation for bowel cleansing, nor is there an optimal method of dealing with inadequate bowel cleansing. This study investigated bowel preparation formulation preferences and responses to bowel preparation situations using surveys. Methods: The study surveyed 221 Korean lower gastrointestinal endoscopists from January to March 2015 and assessed their responses. Results: The analysis indicated that 2-L polyethylene glycol (PEG) plus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…In our study, the recent data revealed that PEG + ascorbic acid regimen was the most widely used. This can be explained by the fact that recent guidelines recommend that CE should be performed as soon as possible (generally after colonoscopy) in patients with overt, obscure bleeding [11], and PEG + ascorbic acid has recently become the most popular regimen for colonoscopy in Korea [19]. The time interval from the ingestion of the bowel preparation regimen to performing CE can be delayed because performing colonoscopy and clinician's decision-making to perform CE after colonoscopy can take time.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the recent data revealed that PEG + ascorbic acid regimen was the most widely used. This can be explained by the fact that recent guidelines recommend that CE should be performed as soon as possible (generally after colonoscopy) in patients with overt, obscure bleeding [11], and PEG + ascorbic acid has recently become the most popular regimen for colonoscopy in Korea [19]. The time interval from the ingestion of the bowel preparation regimen to performing CE can be delayed because performing colonoscopy and clinician's decision-making to perform CE after colonoscopy can take time.…”
Section: Discussionmentioning
confidence: 99%